Farmers’ Education and Farmers’ Wealth in Bangladesh - Abu Zafar Mahmudul Haq (Turkish Journal of Agriculture: Food Science and Technology)
The impact of farmers’ education is examined with a view to evaluate the actual situation of farmers’ education in Bangladesh. Fifty samples were collected from two sub districts of the Gazipur district in Bangladesh. The selection of the study sites and collection of the samples such as the years of schooling of the farm household head, total income, farm size, number of earners of farm families, family size, years of farming experience of farm household head, number of times extension contacts and rice yield were done purposively. It is cleared from the study that education is necessary for farmers to raise their wealth. Results were derived through regression analysis. The study has also shown that size of family and years of farming experience contributed significantly to the wealth accumulation of farmers.